2012
DOI: 10.1143/apex.5.062103
|View full text |Cite
|
Sign up to set email alerts
|

High-Power, Low-Efficiency-Droop Semipolar ($20\bar{2}\bar{1}$) Single-Quantum-Well Blue Light-Emitting Diodes

Abstract: We demonstrate a small-area (0.1 mm 2 ) semipolar (20 2 1) blue (447 nm) light-emitting diode (LED) with high light output power (LOP) and external quantum efficiency (EQE) by utilizing a single 12-nm-thick InGaN quantum well. The LED had pulsed LOPs of 140, 253, 361, and 460 mW, and EQEs of 50.1, 45.3, 43.0, and 41.2%, at current densities of 100, 200, 300, and 400 A/cm 2 , respectively. The device showed little blue shift and had a narrow full width at half maximum (FWHM). Micro-electroluminescence (-EL) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
135
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(138 citation statements)
references
References 29 publications
2
135
1
Order By: Relevance
“…3 for In 0.14 Ga 0.86 N/GaN QWs, the electric field across (11 22) QWs caused by the spontaneous and piezoelectric polarizations in the wells and GaN barriers is roughly estimated to be about 3-times weaker than in polar QWs. The peak shift variation of the PSS-and BulkLEDs is in good agreement with values of $1.3-2.0 nm previously reported for (11 22 33 Thus, these small peak shifts indicate a weak QCSE in semipolar InGaN QWs. Figure 4 shows P opt of the unpackaged PSS-and BulkLEDs measured in DC mode inside an integrating sphere as a function of I inject .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…3 for In 0.14 Ga 0.86 N/GaN QWs, the electric field across (11 22) QWs caused by the spontaneous and piezoelectric polarizations in the wells and GaN barriers is roughly estimated to be about 3-times weaker than in polar QWs. The peak shift variation of the PSS-and BulkLEDs is in good agreement with values of $1.3-2.0 nm previously reported for (11 22 33 Thus, these small peak shifts indicate a weak QCSE in semipolar InGaN QWs. Figure 4 shows P opt of the unpackaged PSS-and BulkLEDs measured in DC mode inside an integrating sphere as a function of I inject .…”
Section: Resultssupporting
confidence: 91%
“…45,46 Generally, the much smaller droop of nonpolar and semipolar LEDs in comparison with polar LEDs has been attributed to the weaker polarization fields. [30][31][32][33]47,48 However, it should be noted that low-efficiency polar LEDs also show a relatively small droop, 35,36 which has been attributed mainly to the strong effect of non-radiative recombination processes. Recently, Davies et al 49 have suggested that the droop is inherent to the carrier density in InGaN QW structures and independent of crystal orientation.…”
Section: Resultsmentioning
confidence: 99%
“…In fact there are examples of LEDs with a low droop published in the recent literature, in these cases they were typically grown on a low dislocation density bulk GaN substrate. 13,14 If we take the cases where the dislocation density is around or below 10 6 cm À2 , we may assume that the dislocation influence on droop can be neglected, and the residual droop in such cases may be understood to be Fig. 3(b) corresponding to areas with lower and higher dislocation density, respectively.…”
Section: -2mentioning
confidence: 99%
“…Also the intrinsic field leads to a spatial separation of electron and hole wave functions, causing a reduced radiative recombination rate [4,6], an effect that can be particularly undesirable for high-efficiency optoelectronic devices. To circumvent these effects arising from the intrinsic built-in fields, which fundamentally are caused by the growth along the polar c axis, significant research has been directed towards the fabrication of semi-and nonpolar structures [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In the case of semi-and nonpolar planes the c axis is at a nonvanishing angle with respect to the growth direction.…”
Section: Introductionmentioning
confidence: 99%